2019
DOI: 10.1080/13572334.2019.1662608
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost policy specialisation, district characteristics and gender. Patterns of committee assignment in Romania

Abstract: Committee assignment can influence the efficiency of legislative work, the success of parties in reaching their policy goals and even the electoral fates of individual legislators. Nevertheless, little is known about this process in the legislatures established in the Central and Eastern European democracies. These legislatures faced severe informational, electoral and partisan challenges which raised the stakes of efficient committee-seat allocation. Simultaneously, most parliaments in the region were endowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…Lastly, the analysis tested an effect of gender on being assigned to low-saliency committees, as was shown by several studies from diverse settings (Chiru, 2019;Espírito-Santo & Sanches, 2020;Goodwin et al, 2020). Such patterns are not visible in the results of the two analysed parliaments.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Lastly, the analysis tested an effect of gender on being assigned to low-saliency committees, as was shown by several studies from diverse settings (Chiru, 2019;Espírito-Santo & Sanches, 2020;Goodwin et al, 2020). Such patterns are not visible in the results of the two analysed parliaments.…”
Section: Resultsmentioning
confidence: 98%
“…This article contributes to the literature that analyses how, within parliaments of parliamentary democracies, who is selected to sit on which committees and with what consequences. Previous studies have suggested a range of factors that explain the process, such as electoral rules and constituency demands, particularly in committees that allow MPs to cater to the interests of voters (Chiru, 2019;Gschwend & Zittel, 2018;Raymond & Holt, 2018;Raymond & Juárez, 2019). MPs' expertise in a committee's jurisdiction was linked to assignments in many institutional contexts (Chiru, 2019;Giannetti, Pedrazzani & Pinto, 2019;Mickler, 2018aMickler, , 2019.…”
Section: The Determinants Of Committee Membership In Belgium and The ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Si bien la teoría informativa ha sido eficaz para explicar la institucionalización del trabajo parlamentario en asambleas que promueven la profesionalización temática de sus integrantes, aún se conoce muy poco sobre cómo operan sus preceptos en aquellas legislaturas que no cuentan con elementos fundamentales de institucionalización, como altos índices de reelección y reglas que recompensen la experiencia previa de los legisladores con cargos de gobierno congresional (para algunas excepciones véanse Santos y Rennó, 2004;Crisp et al, 2009;Oñate y Ortega, 2019;Chiru, 2019).…”
Section: Introductionunclassified